2010
DOI: 10.3390/molecules15021041
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications of Chiral Unsaturated Epoxy Alcohols Prepared by Sharpless Asymmetric Epoxidation

Abstract: An overview of the synthesis and applications of chiral 2,3-epoxy alcohols containing unsaturated chains is presented. One of the fundamental synthetic routes to these compounds is Sharpless asymmetric epoxidation, which is reliable, highly chemoselective and enables easy prediction of the product enantioselectivity. Thus, unsaturated epoxy alcohols are readily obtained by selective oxidation of the allylic double bond in the presence of other carbon-carbon double or triple bonds. The wide availability of epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 99 publications
0
24
0
Order By: Relevance
“…It was observed that all substrates afforded the allylic alcohols in very good yields and good or perfect enantioselectivity (entries 1-13). Higher diastereoselectivities were achieved for enals that lead to A 1,3 strain instead of A 1,2 strain (see entries 6-8 vs. entries [1][2][3][4][5], and an inversion in the diastereoselection of the process was observed. Catalytic asymmetric ethyl transfer to α,β-unsaturated aldehydes in the presence of 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that all substrates afforded the allylic alcohols in very good yields and good or perfect enantioselectivity (entries 1-13). Higher diastereoselectivities were achieved for enals that lead to A 1,3 strain instead of A 1,2 strain (see entries 6-8 vs. entries [1][2][3][4][5], and an inversion in the diastereoselection of the process was observed. Catalytic asymmetric ethyl transfer to α,β-unsaturated aldehydes in the presence of 1.…”
Section: Resultsmentioning
confidence: 99%
“…In 1965 a low level of stereoinduction was already obtained by Henbest, using (+)-peroxycamphoric acid. [2,4] The original Sharpless-Katsuki asymmetric epoxidation requires the use of catalytic amounts of titanium isopropoxide and tartrate ester ligands, tert-butyl hydroperoxide, and molecular sieves. This well-known achievement allowed high stereocontrol to be obtained in the epoxidation of allylic alcohols, including the kinetic resolution (KR) of secondary alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant approach for the asymmetric epoxidation of allylic alcohols is through the titanium-catalyzed Sharpless epoxidation, which can usually achieve the enantioselective epoxidation of primary allylic alcohols catalyzed by l-(+)/d-(−)-diisopropyl tartrate and titanium tetraisopropoxide (Ti(O-i-Pr) 4 ) using tert-butyl hydroperoxide (TBHP) as the oxidant [10,22,69,70]. The absolute configuration of the resulting epoxide can be easily predicted using a rule developed by Sharpless, which correlates to the enantiomer of the tartrate used.…”
Section: Classic Methods For the Asymmetric Epoxidation Of Allylic Almentioning
confidence: 99%
“…Several reviews on the preparation of chiral epoxides have been published [3,7,8,[22][23][24][25][26]. This review does not seek to provide a comprehensive list of all kinds of synthetic/enzymatic methods, but rather to emphasize the potential of biocatalysis in the preparation of chiral epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Along with expanding the scope of catalytic enantioselective epoxidation reactions, the structural diversity of chiral epoxides is increased, [3][4][5][6][7][8] inspiring chemists to develop methods that conduct a selective nucleophilic ring opening of the epoxide. [9][10][11][12][13] To date, a number of reagents and conditions that lead to the regio-and stereocontrolled installation of various nucleophiles have been developed employing Lewis acid catalysis. 14) Among potential nucleophiles, N-nucleophiles, 15) such as amines, azides, amides, carbamates, and so on, have received considerable attention because the reaction allows access to β-amino alcohols, 16,17) which are versatile intermediates for biologically active compounds, chiral ligands, and catalysts.…”
mentioning
confidence: 99%